Developing best practices of Islamic estate planning: A construction based on the perspectives of individuals and estate planning providers - Norazlina Abd Wahab; Selamah Maamor; Zairy Zainol; Suraiya Hashim; Kamarul Azman Mustapha Kamal (ISRA International Journal of Islamic Finance, 2021)
Purpose - This paper aims to develop the best practices of Islamic estate planning for Muslims. Islamic estate planning is a fixed proposal for the management and outlook of an individual's assets throughout their life and upon their passing, created by means of existing Islamic estate planning tools, for instance, farāʾiḍ (inheritance), waṣiyyah (will), hibah (gift) and waqf (endowment). Design/methodology/approach - The paper used an interview method to obtain information on the best practices of Islamic estate planning. Semi-structured interviews were conducted with the respondents and estate planning providers in the northern region of Peninsular Malaysia. The data gathered was analysed using thematic analysis which involved five phases to construct the best practices of Islamic estate planning. Findings - The paper identifies important elements in Islamic estate planning. The elements were outlined as the crucial things that Muslims should do to plan for intergenerational transfer and earning a good share in the hereafter. Research limitations/implications - The first limitation of the paper is that the best practices were developed based on a qualitative method. There is no evidence of its validity, which is a gap that can be explored in the future. Second, it involves the perceptions of two types of respondents (individuals and Islamic estate planning providers), which may be broadened to other related stakeholders such as regulators, in future studies. Originality/value - This paper presents a framework of best practices of Islamic estate planning, it being one of the first studies to do so, which is not only useful and relevant for Malaysian Muslims but also for Muslims in other countries.
Keywords: 330; Best practice; Intergenerational transfer; Islamic estate planning; Malaysia; Semi-structured interview